The Construction of Cucurbit[7]uril-Based Supramolecular Nanomedicine for Glioma Therapy - Chen, Mantao; Hu, Chi; Zhang, Shengxiang; Wu, Dan; Mao, Zhengwei; Zheng, Xiujue (Frontiers in Chemistry, 2022)
Two supramolecular nanomedicines (CB[7]⊃DOX and CB[7]⊃CPT) based on the host–guest recognition between CB[7] and anticancer drugs were constructed. After supramolecular modification, the stability and water solubility of DOX and CPT were greatly improved, and the anticancer activities of chemotherapeutic drugs were effectively maintained. This work provided a simple but efficient method to enrich supramolecular nanomedicines for cancer therapy.